Health information-seeking behavior among women with polycystic ovary syndrome: A scoping review protocol - Xia Chen; Xiaoping Xie; E. Tan; Yingni Liang; Fen Liu; Zhongyu Li; Yinhua Su (PLoS ONE, 2026)
Background Polycystic ovary syndrome (PCOS) is the most common endocrine metabolic disorder among women of childbearing age, and self-management of PCOS patients relies on their ability to obtain health information. The proliferation of digital technologies, particularly social media and health applications, has fundamentally transformed health information-seeking behaviors (HISB) in this population. However, the present information behavior patterns of PCOS patients have not yet been systematically integrated. Objectives This scoping review aims to systematically map the landscape of HISB in women with PCOS by utilizing Wilson’s model of information-seeking behavior as theoretical framework. It seeks to synthesize evidence on their information needs, preferred channels, behavioral types, and key influencing factors. Methods The scoping review will adhere to Arksey and O’Malley’s methodological framework and report following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The review will include English-language literature published from inception up to November 30, 2025, searched through PubMed, Web of Science, Embase (Ovid), CINAHL, Cochrane Library, and APA PsycINFO. To find more relevant studies, we will also search grey literature, the reference lists of the included studies, and related systematic reviews. Two researchers will independently screen titles/abstracts, followed by full-text articles, to assess whether articles meet the inclusion criteria. A third researcher will resolve any discrepancies. Data extraction and narrative synthesis will be structured around the core constructs of Wilson’s model, providing a theory-informed analysis of the evidence. Ethics and dissemination Since this review involves collecting data from existing literature and does not involve human participants, ethical approval is not required. This scoping review will be submitted for publication to a peer reviewed academic journal.